Prospective Evaluation of Surgical Treatment of Humeral Avulsions of the Glenohumeral Ligament. (April 2017) - Provencher, Matthew T.; McCormick, Frank; LeClere, Lance; Sanchez, George; Golijanin, Petar; Anthony, Shawn; Dewing, Christopher B.
Background: Humeral avulsion of the glenohumeral ligament (HAGL) is an infrequent but significant contributor to shoulder dysfunction, instability, and functional loss. Purpose: To prospectively identify patients with HAGL lesions and then conduct retrospective evaluation of the clinical history, examination findings, and surgical outcomes of these patients. Study Design: Case series; Level of evidence, 4. Methods: Over a 6-year period (2006-2011), patients with shoulder dysfunction and a HAGL lesion that was confirmed via magnetic resonance arthrogram (MRA) were prospectively evaluated with a minimum 2-year follow-up. Patient demographics, presentation, examination, and surgical findings were documented. Outcomes of return to activity as well as Western Ontario Shoulder Instability Index (WOSI) and Single Assessment Numeric Evaluation (SANE) scores were recorded at final follow-up. Anterior HAGL (aHAGL) lesions were repaired with a partial subscapularis tenotomy approach, while reverse (rHAGL) lesions were repaired arthroscopically. Results: Of 28 patients, 27 (96%) completed the study requirements at a mean of 36.2 months (range, 24-68 months). The sample contained 12 females (44%) and 15 males (56%), who had a mean age of 24.9 years (range, 18-34 years). The chief complaint reported was pain in 23 patients (85%), while only 4 (15%) patients complained primarily of recurrent instability symptoms. Fourteen patients (52%) had aHAGL lesions, 10 patients (37%) had rHAGL lesions, and 3 patients (11%) had combined aHAGL and rHAGL lesions. Ten patients (37%) had concomitant HAGL lesions and labral tears, whereas 17 patients (63%) had isolated HAGL lesion without labral tear. The 17 patients (63%) with aHAGL lesions or combined lesions underwent a partial subscapularis tenotomy approach, while the remaining 10 patients (37%) with rHAGL lesions underwent arthroscopic surgical repair. After surgery, WOSI outcomes improved from 54% to 88% and SANE outcomes improved from 50% to 91% ( P < .01 for both), with no reports in recurrence of instability symptoms at final follow-up. Conclusion: This study demonstrated that patients with symptomatic HAGL lesions predominantly report shoulder pain and dysfunction, with few chief complaints of recurrent instability complaints. After surgery, patients showed predictable return to full activity, improvement in objective and patient-reported outcomes, and satisfaction with treatment outcome.